FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MITRA KREDIT PG DJOMBANG BARU MEMILIH VARIETAS TEBU SERTA PENGARUHNYA TERHADAP PRODUKSI TEBU - Agung Permadi; Rudi Wibowo; Triana Dewi Hapsari (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
Sugarcane is a strategic commodities, serves as a raw material in sugar production. One of the sugar factories in Indonesia is PG (Sugar Factory) Djombang Baru. To meet the sugarcane milling capacity per day, PG Djombang Baru collaborate by extending its own sugar cane plantations, or sugar cane farmers, one of which is a sugar cane farmer in partnership with  PG Djombang Baru and credit assistance (farmer partner credit). This study aimed to determine: (1) the characteristics of partner farmers credit PG Djombang Baru, (2) the factors that influence farmers' decisions PG Djombang Baru credit partners to choose varieties of early maturity, middle and end of the cane, and (3) whether the selection of varieties cane maturity effect on sugarcane production. Method Selection of research done intentionally (purposive method). The data used are primary data (in 2013) credit partner farmers, sampling methods using simple random sampling were analyzed by: (1) descriptive analysis, (2) logistic regression analysis, (3) analysis of Cobb-Douglas production function. The analysis showed that: (1) the characteristics of farmers credit partners PG Djombang Baru are as follows: most are male sex, age range 40-61 years, Junior High School up to Senior High School or equivalent, sugarcane farming experience more than 8 years, the land is a land with a lease, and plant more than one type of maturity varieties of sugarcane, (2) the variables that significantly affect the decision making of farmers in choosing varieties ripening and labor sugarcane production and sugar cane; (3) The variables that significantly affect the production of sugar cane land area and a dummy variable maturity end of the cane. Keyword : sugarcane, varieties, production, logistic regression